KNOWLEDGE SHARING MODEL TO IMPROVE QIRA’AH SKILLS FOR LIBRARIANS OF IAIN PEKALONGAN - Alghiffary, Muhammad; Isbah, Faliqul; Sa’diah, Namirotun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to formulate a SECI-based knowledge sharing model, specifically in the socialization and externalization stages, to improve maharah qirā’ah (Arabic reading competence) for librarians at IAIN Pekalongan in managing Arabic language collections. The background of the study shows that proficiency in Arabic is a fundamental requirement in PTKI libraries; however, various errors in acquisition, searching, and processing of collections still occur due to librarians' limited reading abilities. Using a qualitative case study approach, data were collected through semi-structured interviews, participant observation, and documentation studies with six librarians and two supporting informants. At the socialization stage, the study found five prominent tacit knowledge constraints: difficulty distinguishing types of Arabic collections, difficulty reading Arabic text without diacritics, lack of understanding of bibliographic terms, difficulty reading Arabic numerals—especially in the thousands format—and inability to identify bibliographic information in damaged or incomplete books. These findings indicate that limitations in maharah qirā’ah directly affect the accuracy of cataloging and information services. At the externalization stage, all these constraints were converted into explicit knowledge needs in the form of bibliographic analysis materials, basic rules for reading unvowelled Arabic, a list of technical terms, Arabic numeral materials, and techniques for quickly identifying damaged books. This process produces a learning material design that aligns with the real needs of librarians. The study concludes that the first two stages of the SECI model are capable of building a structured foundation for developing librarians' reading competencies and paving the way for the formulation of a more comprehensive knowledge sharing model in the subsequent stages.